The State of Practice of Prefabrication - Bishara Mikhail, George (My University, 2014)
In today?s construction industry, electrical contractors must think about adopting non-conventional construction methods such as prefab in order to improve their performance and to face the continuous challenges they encounter. Challenges facing electrical contractors today include: low labor productivity levels, low and fluctuating profit margins and frequent schedule compressions. Multiple studies conducted by other researchers revealed that the appropriate use of prefab for many trades has a positive impact on project performance. In general, prefab has the potential to positively impact the project in the following project factors: cost, quality, schedule, safety and productivity. In addition, these studies discussed some impediments for the use of prefab. Common impediments for the use of prefab include increased engineering requirements, transportation considerations and organizational requirements. However, there is a gap in the literature about prefab in the electrical contracting industry. No recent research exists that is specific to the electrical contracting industry. Based on the literature review, a comprehensive survey about prefab was prepared. The survey was generated online and emailed to electrical contractors using Qualtrics, which is a web-based survey service. 142 electrical contractors representing diverse regions of the United States and Canada responded to the survey. A substantial variety of electrical works conducted by electrical contractors are represented. In addition, small, medium and large size companies are well represented in these responses. Of the 142 electrical contractors who responded to the survey, this research showed that 74 percent currently use prefab. The majority of these current-users began adopting prefab in their companies over five years ago. However, 63 percent of users spend only 1 to 9 percent of their company?s labor hours on prefab. Electrical contractors reported that prefab can help in improving labor productivity as they estimated that one productive hour in the shop equals (on average) 2.2 hours in the field. Finally, this study showed that electrical contractors will still have disparate use of prefab during the next two years. On average, users and non-users estimated prefab would be used on 37 percent of electrical construction projects during that time. However, electrical contractors currently using prefab are planning on using prefab on more than 75 percent of their projects during the next two years and 72 percent of electrical contractors that are not currently using prefab anticipate starting use in the next two years. This seems to indicate that as electrical contractors learn to use prefab they use it with increasing frequency which implies that the use of prefab will continue to grow.